Waste Generation and Management Practices in BSCIC Mymensingh - Rahman, MS; Datta, S; Islam, S (Journal of Environmental Science and Natural Resources, 2015)
The present study was undertaken to quantify the waste generation in BSCIC, Mymensingh and to identify the waste disposal and management system for forecasting the environmental impacts of these wastes. Data were collected through a pre-tested questionnaire from 50 industries and a recycling plant divided in categories based on their daily production capacity. The study shows that total waste generation was 9758 kg/day of which 34.53% wastes were from puffed rice mills, 27.42% from mustard oil industries, 8.89% from fertilizer and pesticide industries, 6.8% from flour mills, 6.49% from bakery food industries, 2.83% from coconut oil mills, and 13.04% from all other industries. Small, medium and large category industries produced 1223 kg/day, 3115 kg/day and 5420 kg/day of wastes, respectively. Most of the generated wastes were solid and liquid. Some industries recycled the wastes as a part of manufacturing process. It was found that 44.19% industries sell wastes to poultry, fisheries and livestock personnel for making profit, 39.53% use municipal waste as management system, 13.95% recycle their wastes onsite or sending the wastes to waste recycling plant, and 2.32% industries sell the wastes for biomass burner fuel. Roadside solid wastes are picked up by municipal waste management system and liquid effluents pass its way through the municipal drains to the Brahmaputra River. Leftover wastes are not significant enough to cause environmental degradation. No serious complains about health hazard or pollution in environment was found from the surrounding community. DOI: http://dx.doi.org/10.3329/jesnr.v7i1.22143 J. Environ. Sci. & Natural Resources, 7(1): 47-51 2014